Attractor comparison analysis for characterizing vertical upward oil-gas-water three-phase flow - 赵俊英 金宁德 高忠科 杜萌 王振亚 (Chinese physics B, 2014)
We investigate the dynamic characteristics of oil-gas-water three-phase flow in terms of chaotic attractor comparison. In particular, we extract a statistic to characterize the dynamical difference in attractor probability distribution. We first take time series from Logistic chaotic system with different parameters as examples to demonstrate the effectiveness of the method. Then we use this method to investigate the experimental signals from oil-gas-water three-phase flow. The results indicate that the extracted statistic is very sensitive to the change of flow parameters and can gain a quantitatively insight into the dynamic characteristics of different flow patterns.